Pengaruh Learning Organization terhadap Kinerja dan Kepuasan Kerja PPPK: Bukti Empiris dari Badan Kepegawaian Negara - Ika Ardhile Nugrahaningtyas; Naili Zulianti (JOM, 2026)
This study examines the effect of learning organization (LO) on job satisfaction and individual performance of Government Employees under Work Agreements (PPPK) at Indonesia's National Civil Service Agency (BKN), as well as the mediating role of job satisfaction in this relationship. Empirical evidence on LO has been largely concentrated in private-sector and Western settings, leaving its nomological network among contract-based public sector employees in developing countries insufficiently examined. Drawing on Social Exchange Theory (SET) and the Job Demands-Resources (JD-R) Model, this study proposes that LO enhances both job satisfaction and performance, with job satisfaction functioning as a mediating mechanism. A quantitative, cross-sectional survey was administered to 107 PPPK across all work units at BKN through total sampling. LO was measured using the adapted DLOQ (43 items), performance using the IWPQ (18 items), and job satisfaction using a three-item global evaluation instrument. Data were analyzed via PLS-SEM using SmartPLS 4. All four hypotheses were supported: LO positively influenced performance (β = 0.424, p < 0.001) and job satisfaction (β = 0.437, p < 0.001); job satisfaction positively influenced performance (β = 0.499, p < 0.001); and job satisfaction significantly mediated the LO-performance relationship (β = 0.219, p < 0.001). These findings extend LO theory to contract-based public sector employment and offer actionable implications for PPPK competency development policy.